MEKANISME PENEKANAN EKSPRESI N-RAS EKSTRAK KULIT JERUK KEPROK (Citrus reticulata) SEBAGAI AGEN KEMOPREVENTIF - N., Perdana Adhi; D., Andita Pra; P.K.W., Diah Ayu; Riyanto, Sugeng; Meiyanto, Edy (Jurnal Farmasi Indonesia, 2009)
One targeting point of cancer treatment, especially liver cancer is the suppression of N-Ras expression, inhibition of c-Src activity and CYP1A2 in the liver cells. The aim of the research in to explore the anticarcinogenesis effect of the ethanolic extract of C. reticulata peel through suppression of N-ras expression and the binding afinity and interaction of polimetoksiflavon compound found in the peel of Citrus Reticulata, namely tangeretin and nobiletin to the target protein using molecular docking. Geometry structure optimization tangeretin and nobiletin were done with the software Molecular Operating Environment (MOE) for Windows. The optimum structure conformation of tangeretin and nobiletin were approached using semiempirik AMBER99 method. The process of docking of the test compound to the bindingsite c-Src (PDB ID: 1FMK) and CYP1A2 (PDB ID: 1AE4) were done using the software Molecular Operating        Environment (MOE) for Windows in the conditions without water. From the docking process found that the lowest scoring value is tangeretin in conditions without water.  Docking Results of tangeretin compared with the experimental ligan in the target CYP1A2, shows the interaction of tangeretin stronger than the interaction of ligan an α-naphtoflavon. Meanwhile, the target protein, c-Src, interaction endogenous ligan (ATP) is much stronger than the interaction with the test compound and ligan comparison Imatinib. Therefore, it is estimated that the mechanism of liver cancer hepar inhibition in molecular docking is through CYP1A2 inhibition. ABSTRAK Salah satu titik tangkap pengobatan kanker khususnya kanker hepar adalah penekanan ekspresi N-Ras, penghambatan protein c-Src dan aktivitas CYP1A2 di hepar.  Penelitian ini bertujuan untuk mengetahui afinitas dan interaksi senyawa berkerangka polimetoksiflavon pada kulit jeruk keprok (Citrus reticulata) yaitu tangeretin dan nobiletin terhadap protein target tersebut menggunakan molecular docking. Optimasi geometri struktur tangeretin dan nobiletin dilakukan dengan piranti lunak Molecular Operating Environment for Windows.  Konformasi optimum tangeretin dan nobiletin dihasilkan menggunakan metode semiempirik AMBER99. Kemudian dilakukan proses docking senyawa uji dengan bindingsite c-Src (PDB ID : 1FMK) dan CYP1A2 (PDB ID : 1AE4) menggunakan piranti lunak Molecular Operating Environment for Windows dalam kondisi tanpa air. Dari hasil yang diperoleh dapat diperkirakan bahwa mekanisme penghambatan kanker hepar secara docking molekuler adalah melalui penghambatan CYP1A2